Quality of Air Transportation Services in Supporting Accessibility of Tourist Destinations in West Java Province - Fernando, Fernando; Simangunsong, Fernandes; Rusfiana, Yudi; Achmad, Mansyur (ARISTO, 2025)
Airport transportation is one of the backbones of national transportation and connectivity. The government has issued regulations related to Minimum Service Standards for Air Transportation Passengers which have an important role in regulating and ensuring the quality of service provided by airport management to consumers or users of services. West Java itself has three airports as transportation access in the accessibility of tourist destinations, namely Husein Sastra Negara Airport, Kertajati Airport and Nusawiru Airport. The purpose of this study is to analyze the Quality of Air Transportation Services in Supporting the Accessibility of Tourist Destinations in West Java Province. The research method used in this study is a descriptive method with a qualitative approach. Data collection was carried out through in-depth interviews, participant observation and document collection and studies. The results of this study explain that the Quality of Air Transportation Services in Supporting the Accessibility of Tourist Destinations in West Java Province at Nusawiru Airport is not optimal due to several things including facilities and infrastructure that need to be rejuvenated so that they can support excellent service. Supporting factors Nusawiru Airport has a strategic position as the only airport located in the Southern West Java, which is an alternative gateway to Tourist Destinations in West Java. As a strategic national tourism area to become a world tourist destination. Inhibiting factors The frequency of flight services from and to Nusawiru cannot be ensured to be routinely available every day, so that income from traffic is still low. Then another inhibiting factor is the financing factor for the operation of Nusawiru Airport.